SCAFFOLDING, MULTILITERACIES, AND READING CIRCLES - Cumming‐Potvin, Wendy (Canadian Journal of Education/Revue canadienne de l’éducation, 2007)
In this qualitative study, that took place in a coeducational government school in Western Australia, I adopt a social‐constructivist perspective of learning (Rogoff, 1990; Vygotsky, 1986) to examine reading in an elementary classroom. The focus of this article is Nicholas, a grade‐7 boy, who was identified as challenged by the literacy curriculum. The analysis utilizes a multiliteracies framework (The New London Group, 2000) and the four resources reading model (Luke & Freebody, 1999) to interpret Nicholas’ progress during reading circles. Results suggest that multiliteracies, which interweave scaffolding, diverse texts, and meaningful tasks, can encourage agency for student learning. Key words: literacy identity, scaffolding, reading, pedagogy of multiliteracies, reading resources model, socio‐economically disadvantaged students, school literacy‐ assessment Dans cette étude quantitative, qui a été menée dans une école gouvernementale mixte en Australie‐Occidentale, l’auteure adopte un point de vue socioconstructiviste sur l’apprentissage (Rogoff, 1990 ; Vygotsky, 1986) en vue d’analyser l’aptitude à la lecture dans une classe du primaire. L’article porte essentiellement sur Nicholas, un garçon de 7e année, aux prises avec des difficultés par rapport au programme de littératie. L’analyse fait appel à un cadre de multilittératies (The New London Group, 2000) et à un modèle de lecture axé sur quatre ressources (Luke & Freebody, 1999) en vue d’interpréter les progrès de Nicholas au cours des cercles de lecture. Les résultats donnent à penser que les multilittératies, qui combinent soutien à l’apprentissage, textes divers et tâches intéressantes, peuvent encourager les élèves à apprendre. Mots clés : littératie, soutien à l’apprentissage, lecture, pédagogie des multilittératies, élèves défavorisés, évaluation de la littératie à l’école